Pelatihan Kreatifitas Pembuatan Alat Permainan Edukatif Bagi Orang Tua Siswa PAUD - Ni Made Sulastri; Dewi Rayani (Abdi Masyarakat, 2019)
The purpose of this community service activity is to increase the creativity of making educational game tools for parents of students' parents. This is based on several observations and found indications that most parents do not use their time well when activities wait for children to go home from school, parents only spend time without meaningful activities they usually spend just by chatting with other parents, sometimes teachers also accompany their children to learn in the classroom where these activities greatly interfere with the ongoing teaching and learning process. As a result of the routine and busyness of the parents, it is necessary to have activities that can be useful for parents and also for children's growth and development. Because in supporting the growth and development of children, educational tools are also needed that can be made by the teacher or parents themselves, so it is necessary to provide a creative training to develop educational games for parents. The method used in community service activities is in the form of counseling / education. Involved parents as much as 20. Community service activities include the provision of material on how to develop creativity to make educational games